Conceptual Metaphors in Kelly Andrew's Your Blood, My Bones (2024) - Savira Nurlaily; Moh. Supardi; Saefudin; Muhammad Farkhan (Journal of Translation, Linguistics and Literature, 2026)
This study discusses conceptual metaphors found in Your Blood, My Bones (2024) by Kelly Andrew. The purpose of this qualitative research is to identify metaphors in the novel and categorize them based on Conceptual Metaphor Theory by George Lakoff and Mark Johnson from a cognitive semantics approach. Moreover, it aims to analyze conceptual mappings essential in understanding the relations between the source and target domains, as well as the meaning these metaphors convey. Additionally, this research relies on the Master Metaphor List, which provides a broader range of conceptual metaphors. Textual data is gathered by highlighting expressions with metaphorical meanings and determining its source and target domains. The data are classified into two types according to the theory, resulting in ontological metaphors as the most common, followed by orientational metaphors. The results show that metaphors are not merely used to embellish words but to understand even the most basic concepts, including emotions, perspective of time, form of communication, visual field, and understanding of life itself.